Metaphysics or ontology? - Jaroszyński, Piotr (Value inquiry book series, Gilson studies, 2018)
Metaphysics or Ontology? treats the evolution of the object of metaphysics from being, to the concept of being, to, finally, the object (thought). Possible being must be non-contradictory, but an object of thought includes anything a human being can think, including contradictions and nothingness. When the concept of being, or object of thought, replaces existence as the object of metaphysics, it becomes something other than metaphysics--ontology, or something beyond ontology. However, ontology cannot examine existence because it only investigates concepts and possibility. Only classical metaphysics investigates reality qua reality. This book masterfully treats the history of this controversy and many other important metaphysical questions raised over the centuries.